Increasing student engagement and retention using mobile applications : smartphones, Skype and texting technologies - Wankel, Laura A.; Blessinger, Patrick; Stanaityte, Jurate; Washington, Neil (Cutting-edge technologies in higher education ;, 2013)
Examines new research on how mobile technologies are being used in higher education to increase learner engagement in an epoch of increasing globalization and diversity. These enabling technologies are reshaping and reframing the practice of teaching and learning in higher education. Through case studies, surveys, and literature reviews, this volume will examine how mobile technologies are being used to improve teamwork and leadership skills in students, to create engaging communities of practice, and how these technologies are being used to create inter-cultural and global experiences. This volume will also discuss frameworks for adopting and deploying these technologies.